Implementasi Aplikasi Identitas Kependudukan Digital (IKD) Dalam Menunjang Pelayanan Publik Masyarakat Di Kecamatan Tambaksari - Salsa Bella, Vivtania; Widodo, Djoko (Universitas Gajah Putih, 2024)
In the field of population administration public services, accompanied by the increasing development of technology in Indonesia, various new breakthroughs have emerged, one of which is from the Director General of Dukcapil, Ministry of Home Affairs, including the Digital Population Identity (IKD) application. IKD is the digitization of population documents used by people in Indonesia who have electronic KTPs. In this IKD, residents who have activated will receive electronic information used to represent population documents and personal data of residents. The aim of the IKD is to follow the use of information and communication technology related to digitalization, increase the use of digitalization, accelerate the exchange of public and private services in digital form and provide security of IKD ownership. In the implementation process, of course the Director General of Dukcapil is assisted by the government of each district and city, one of which is the City of Surabaya. The Surabaya City Population and Civil Registry Dispendukcapil has implemented the IKD implementation with assistance from the government in sub-districts and sub-districts, such as in Tambaksari Subdistrict. The IKD implementation process in Tambaksari sub-district takes into account aspects of George C. Edward III's implementation theory including communication, resources, disposition or behavior, and bureaucratic structure. By paying attention to these aspects and IKD being a new breakthrough, it is hoped that the level of knowledge and mastery of the Tambaksari District community regarding what IKD is will increase and implementation can run optimally to support the public service process for the people in Tambaksari Subdistrict.